Demographic and Socioeconomic Factors, Including Workers’ Compensation, as Predictors of Monocular Blindness After Open Globe Injuries - Chen C; Malek DA; Greenfield JA; Yuan Z; Cavuoto KM (Clinical Ophthalmology, 2025)
Constance Chen, Davina A Malek, Jason A Greenfield, Zhuochen Yuan, Kara M Cavuoto Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: Kara M Cavuoto, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, 900 NW 17th Street, Miami, FL, 33136, USA, Tel +1 305 326 6324, Fax +1 305 547 3675, Email kcavuoto@med.miami.eduObjective: To investigate the effect of demographic factors in predicting monocular blindness in patients after open globe injury (OGI) in a large tertiary ophthalmology center.Methods: A retrospective chart review of patients with OGI. Clinical data collected were visual acuity, presence of globe rupture, perforating injury, and rapid afferent pupillary defect. Demographic factors included race, sex, time to follow-up, and insurance status. Primary outcome is monocular blindness with visual acuity worse than 20/200 at the last follow-up visit. Logistic regression models and univariable and multivariable analysis were performed to examine the effect of demographic characteristics.Results: Four hundred and forty-three patients (mean age: 48 ± 22.5 years) were included and the majority (348, 78%) were male. Patients of Black race and females were approximately twice as likely to have monocular blindness (OR: 1.9 [1.2– 3.0]; p = 0.005 and OR: 2.0 [1.3– 3.2]; p = 0.003, respectively). Older individuals were more likely (OR: 1.3 [1.2– 1.4]; p < 0.001) to have worse visual outcomes per each decade of life. Patients with workers’ compensation were almost half as likely to have monocular blindness (OR: 0.41 [0.21– 0.79]; p = 0.008), and also had significantly greater number of clinic visits (mean: 15.7 visits) than those without (mean: 11.7 visits, p = 0.02).Conclusion: Black race, older patients, and females were more likely to experience monocular blindness. Patients with workers’ compensation and being Hispanic or Latino race were associated with decreased risk of monocular blindness. Combined racial and ethnic analyses showed persistent effects of non-Hispanic Blacks experiencing poor outcomes. These findings emphasize the need for a multifactorial approach in evaluating ocular trauma.Keywords: open globe injury, visual outcome, demographic, insurance, workers’ compensation, ocular trauma score